Does environmental and renewable energy R&D help to achieve carbon neutrality target? A case of the US economy. (15th October 2021) - Shao, Xuefeng; Zhong, Yifan; Li, Yameng; Altuntaş, Mehmet
Abstract: The current study investigates carbon neutrality targets for the US's case while analyzing the role of environmental-related research and development (ERR&D) and renewable energy research and development (RER&D). This study also considered economic growth (GDP) and energy productivity (EP) as controlled variables. Utilizing the time series data over the period from 1990 to 2019, this study used various econometric approaches, such as unit root tests and cointegration tests for stationarity and the long-run association between variables, respectively. This study's main econometric regression tools, such as dynamic ordinary least square (DOLS) and fully modified ordinary least square (FMOLS), are utilized. The empirical findings reveal that economic growth played a negative role in achieving carbon neutrality targets. However, EP, RER&D, and ERR&D positively contribute to carbon neutrality target achievement by reducing atmospheric CO2 emissions. Moreover, this study found a cointegration relationship between the study variables. The bidirectional causality is found between ERR&D and CO2 emissions, while a unidirectional causality is observed, running from exogenous variables towards CO2 emissions. Based on the empirical findings, this study recommends expanding the investment and expenditures in both ERR&D and RER&D sectors to attain carbon neutrality. Highlights: The current study investigates carbon neutrality targets for the US's case. The study analyses environment-related research and development (ERR&D). The study used advanced econometric methods for analysis. The results show ERR&D positively contributes to the carbon neutrality target. The bidirectional causality is found between ERR&D and CO2 emissions.